Crizotinib and Sunitinib Induce Hepatotoxicity and Mitochondrial Apoptosis in L02 Cells via ROS and Nrf2 Signaling Pathway - Guo, Lin; Gong, Hui; Tang, Ting-Li; Zhang, Bi-Kui; Zhang, Lei-Yi; Yan, Miao (Frontiers in Pharmacology, 2021)
Considerable attention has been raised on crizotinib- and sunitinib-induced hepatotoxicity, but the underlying mechanisms need further examination. In addition, limited therapeutic strategies exist to reduce the liver damage caused by crizotinib and sunitinib. This study investigated the mechanisms of crizotinib- and sunitinib-induced hepatotoxicity and the potential mitigation through ROS and Nrf2 signaling. Firstly, crizotinib and sunitinib reduced cell viability in human liver cells (L02 cells) and triggered dramatic liver injury in mice. Subsequently, we found that crizotinib and sunitinib activated the oxidative stress response (decreased level of GPx and SOD, and increased MDA content) in vivo. Crizotinib and sunitinib also stimulated hepatocyte mitochondrial apoptosis and necrosis in L02 cells in a dose-dependent manner. In vivo studies further confirmed that crizotinib and sunitinib decreased mitochondrial membrane potential and activated apoptosis-associated proteins (cleaved-PARP, cleaved caspase3, cytochrome c, Bcl2 and Bax). Furthermore, mechanistic investigations demonstrated that crizotinib and sunitinib accumulated ROS and inhibited Nrf2 signaling, and that ROS scavenger NAC and Nrf2 agonist tBHQ alleviated the extent of cell damage and the mitochondrial apoptosis during crizotinib- and sunitinib-induced hepatotoxicity in L02 cells. Collectively, these findings indicated that NAC and tBHQ play the crucial roles in crizotinib- and sunitinib-induced mitochondrial apoptosis via the regulation of oxidative stress.